2019
DOI: 10.1136/bmjopen-2018-028736
|View full text |Cite
|
Sign up to set email alerts
|

Association of the frequency of spicy food intake and the risk of abdominal obesity in rural Chinese adults: a cross-sectional study

Abstract: ObjectivesRecent data relating to the association between spicy food intake frequency and abdominal obesity are limited, especially in low-income areas. Therefore, the study explored the relationship between spicy food intake frequency and abdominal obesity, and assessed the role of energy intake as a mediator of these associations in a rural Chinese adult population.DesignCross-sectional study.SettingRural Chinese adult population.ParticipantsSubjects from Henan Rural Cohort Study (n=28 773).Primary outcome m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 40 publications
4
13
0
1
Order By: Relevance
“…Consistent with the CKB study, a study conducted in Henan Province of China revealed that spicy flavor and spicy food frequency were associated with a higher risk of general obesity in Chinese rural populations ( 23 ). Additionally, a cross-sectional study suggested that spicy food intake might increase abdominal obesity risk by increasing energy intake ( 42 ). It is worth noting that many studies have demonstrated that obesity is an independent contributor to hyperuricemia in many countries, such as in United States, China, Japan, and Korea ( 41 , 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the CKB study, a study conducted in Henan Province of China revealed that spicy flavor and spicy food frequency were associated with a higher risk of general obesity in Chinese rural populations ( 23 ). Additionally, a cross-sectional study suggested that spicy food intake might increase abdominal obesity risk by increasing energy intake ( 42 ). It is worth noting that many studies have demonstrated that obesity is an independent contributor to hyperuricemia in many countries, such as in United States, China, Japan, and Korea ( 41 , 43 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…This statistics highlights that Pakistani people usually consumes more spice in food on daily basis, and spicy food can influences the health outcomes like oral ulceration. 17,18 Previous researches have also shown that stress and family history of risk factors of oral ulcerations. 1,19 In current study, we found that most of the students knew that stress and positive family history of oral ulceration are risk factors of ulcerations.…”
Section: Discussionmentioning
confidence: 99%
“…There is also debate about whether nicotine, which is found in cigarettes, or one of the tobacco product's constituents, causes the defensive effect. 18,24 Nicotine is more systemically consumed in cigarettes than in nonsmokers, so the former may have a lower defensive benefit than the latter. 18,[24][25][26] In our study we found that 74% of the students thought that smoking can cause oral ulcerations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline information of participants including sociodemographic characteristics (age and gender), socioeconomic status (educational level, marital status, average monthly income), and lifestyles (smoking and drinking status, physical activity, diets) were collected via a structured questionnaire by trained investigator [16]. Speci cally, age was divided into 18-, 45-, and 65-years; educational level were divided into elementary school or below, junior school, and high school or above; marital status was divided into married/cohabitation and unmarried/divorced/widowed; average monthly income was divided into <¥500, ¥500-, and ¥1000-; both smoking-and drinking status were divided into never, former, and current; physical activity measured by metabolic equivalent (MET) hours per week was classi ed into low, moderate, and high [17]; more vegetables and fruits intake was de ned as one person who ate vegetables and fruits over 500 g/day averagely and high fat diet was de ned as one person who ate fat over 75 g/day averagely; body mass index (BMI) was calculated by height and weight, which were measured to the nearest 0.1cm and 0.1kg through standard measuring equipment, respectively.…”
Section: Covariate Measurementmentioning
confidence: 99%